(untitled) (The Pakistan Development Review, 2012)
This study attempts to analyse the impact of fiscal decentralisation on economic growth. It also examines the complementarity between fiscal decentralisation and democratic institutions in promoting growth. The modelling framework is the endogenous growth model augmented with measures of fiscal decentralisation through democratic institutions. To capture the multidimensionality, three different measures of fiscal decentralisation are used. The overall analysis shows that revenue decentralisation promotes economic growth while expenditure decentralisation retards economic growth. Composite decentralisation positively influences economic growth implying that simultaneous decentralisation of revenue and expenditure reinforce each other to promote economic growth. Analysis also shows that democratic institutions play a significant role in realising the benefits of fiscal decentralisation. Various policy implications emerge from this study. JEL Classification: C26, E02, H11, H72, O11 Keywords: Fiscal Decentralisation, Democracy, Economic Growth, Pakistan